Entrepreneurial Orientation and Entrepreneurial Intention in Generation Z: The Mediating Role of Entrepreneurial Education and Parenting Style - Amanda Setiorini; Harsono Yoewono; Kane Evan (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Youth unemployment in Indonesia remains a pressing challenge, demanding a paradigm shift from job seeking to job creation through entrepreneurship development. Objective: This study examines the mediating roles of Entrepreneurial Education (EE) and Parenting Style (PS) in the relationship between the dimensions of Entrepreneurial Orientation (EO) and Entrepreneurial Intention (EI) among Generation Z in Indonesia. Methods: A quantitative approach using SEM-PLS with SmartPLS 3.2.9 was applied to data collected from 327 university students. Results: The findings indicate that EE is a significant mediator and exerts a strong direct effect on EI. However, the mediating effect of EE is selective, operating only through the Proactiveness and Competitive Aggressiveness dimensions of EO. PS neither mediates the EO–EI relationship nor significantly predicts EI. Conclusion: The formal educational environment plays a more dominant role than the family environment in shaping EI among Generation Z. Institutions should design EE curricula that explicitly target Proactiveness and Competitive Aggressiveness. The model explains 44% of the variance in EI; future research should incorporate variables such as entrepreneurial self-efficacy and social support.